Transformações socioprodutivas na cadeia do leite: mudanças na base ecológica e informalidade como estratégias na agricultura familiar de Santa Maria/RS - Marcon, Gian (2019)
Dairy production and family farming in Brazil cannot be analyzed separately from each other due to the importance and protagonism between both for the Brazilian rural reality. However, there were changes in the milk chain, especially since the 1990s, that transformed some economic, productive and social aspects within the national, state and municipal reality. In this context, the main consequence is the exclusion of families from the activity, what brought up two perspectives: the first one defends that the way for farmers to survive in the activity and stay living in their lands is through increased productivity, thus making them more competitive against in the market economy. On the other hand, the second perspective represents a criticism of the first view, understanding that family farming has a wide range of features that characterize it, so it is necessary to think and build production systems more appropriated to each reality, not solely based on increasing productivity. In line with the second perspective, this research study sought to identify and analyze the transformations occurred in the dairy sector, especially since the country's economic opening period in the 1990s. Thus, this dissertation initially analyzed the historical changes in the sector and their consequences, both in national and local scale. In the sequence, the strategies adopted by some families of Santa Maria/RS were analyzed, being possible to consider as within the context of analysis the strategy of ecological production, using the Voisin grazing management and homeopathy, and the strategy called informality. Finally, it was conducted a reflection on the concept of quality, and its implications for the rural environment and the dairy activity. It was possible to identify and understand the current conformation of the dairy production in the municipality of Santa Maria/RS, the reduction in the number of families linked to this activity, and the infeasibility of local initiatives. It is concluded that the strategies of production with ecological basis and informal marketing are of great importance to the social reproduction of families, as well for their permanence in the dairy activity and rural areas. Different views on the quality of milk, from different chain components, may result in different consequences for families and for the future of the activity in Santa Maria/RS. Thus, there is a need for the broadening of the concept of milk quality, considering aspects encompassed within the production with ecological basis of Santa Maria/RS, and as a proposal to change it in matters involving the marketing of raw milk and its derivatives.